Engine performance and exhaust gas emissions of methanol and ethanol-diesel blends - SAYIN, CENK (ELSEVIER SCI LTD, 2010)
In this study, the effects of methanol-diesel (M5, M10) and ethanol-diesel (E5, E10) fuel blends on the performance and exhaust emissions were experimentally investigated. For this work, a single cylinder, four-stroke, direct injection, naturally aspirated diesel engine was used. The tests were performed by varying the engine speed between 1000 and 1800 rpm while keeping the engine torque at 30 Nm. The results showed that brake specific fuel consumption and emissions of nitrogen oxides increased while brake thermal efficiency, smoke opacity, emissions of carbon monoxide and total hydrocarbon decreased with methanol-diesel and ethanol-diesel fuel blends. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Exhaust emissions; Engine performance; Methanol; Ethanol; FUEL BLENDS